Giovanni Battista Vitali’s Violone in the Accademia - Sanguineti, Alessandro (Journal of the Society for Musicology in Ireland, 2017)
This article discusses the background and content of Se le passioni amorose si debbano scoprire all’amico, ‘Olà, saggi, tacete’, an accademia set by Giovanni Battista Vitali, preserved in the Biblioteca Estense Universitaria, Modena, Mus. E. 245. Presumably performed during the period 1690–92, this special type of cantata includes one of the earliest examples, hitherto unnoticed, of a solo-obbligato bass-violin aria. Such arias were increasingly included in operas and oratorios composed in northern Italy from the late 1680s, but rarely in cantatas, and the present article explores the possible reasons behind the introduction of the bass violin as an obbligato instrument in dramatic settings. The aria in question, ‘Non hà compagno amor’ for bass and obbligato violone (the accademia’s second aria), is here examined and provided, in transcription, as a supplement to this article. The use of the Modenese tuning BBflat–F–c–g and of double-stops and chords closely relate Vitali’s writing in this aria to his other music for violone. A study of the aria’s musical content provides further confirmation of the organological type of Vitali’s violone, clearly a vertically-played bass violin that corresponds to the violoncello. Indeed, there are striking similarities between Vitali’s aria and the solo-obbligato violoncello arias in operas and oratorios by Domenico Gabrielli and Giovanni Bononcini.